'Our jolly marin wear': The queer fashionability of the sailor uniform in interwar France and Britain. Issue 2 (1st March 2016) - Stephenson, Andrew
Examining autobiographies, letters, newspaper reports and photographs, this article argues that French sailor wear with its military exoticism and gender-blurring possibilities was adopted by fashionable metropolitan British and French groups in the interwar years as a recognizable signifier of an emerging gay and bisexual identity. The appropriation of the French military uniform by gay and bisexual men and by lesbians was tied, on the one hand, to their firsthand experience of travel to the Mediterranean coast, and to ideas about the Mediterranean ports as places of sexual liberalism and bohemianism that featured in contemporary ballet and the theatre. On the other hand, such promiscuous associations also drew upon popular mythologies about the sailor's erotic appeal and his voracious sexual appetite that were circulating within contemporary French novels, the illustrated press, popular films and songs. As the appropriation of the naval uniform became visible in photographs documenting its growing fashionability in gay clubs, fancy dress balls and parties in Paris and London, sailor wear registered as queerly resonant to its wearers and admirers, leading to the French sailor becoming a recognizable and much-admired promiscuous gay icon.